Detection of phenazines from UPMP3 strain of Pseudomonas aeruginosa and its antagonistic effects against Ganoderma boninense - Parvin, Waheeda; Othman, Radziah; Jaafar, Hawa; Wong, Mui-Yun (Friends Science Publishers, 2016)
To identify the phenazine antibiotics from the selected UPMP3 strain of Pseudomonas aeruginosa and assessment of its antagonistic activity of Ganoderma boninense, three antibiotics phenazine (PHZ), phenazine-l-carboxylic acid (PCA) and pyocyanin (PYO) were extracted from the bacterial fermented broth using benzene and chloroform and detected through High-performance liquid chromatography (HPLC). The effects of three antibiotics on suppressing mycelial growth of G. boninense were assayed. The maximum amount of PHZ, PCA and PYO were recorded as 1.36, 9.62 and 15.48 μg/mL, respectively and showed in vitro antagonistic activity against G. boninense. Phenazine was found to be more effective than PCA and PYO to inhibit the mycelial growth of G. boninense. It was 100% for PHZ at 1.0 mg/mL, while 78.61% for PCA and 91.87% for PYO after 7 days of incubation. Phenazine, PCA and PYO were identified as first time from oil palm rhizospheric UPMP3 strain of P. aeruginosa. The results indicated that the identified PHZ, PCA and PYO compound had good antifungal activity against G. boninense, however the PHZ can be developed as an ideal biofungicide for the control basal stem rot disease of oil palm and helps to overcome the concerns about the residual effects of synthetic fungicides.